Green nudging - A key against littering? Behavioral economic measures for cleaner cities - Jennifer Potthoff (Institut der deutschen Wirtschaft (IW), 2023)
The demand for cleanliness in cities is increasing: "Littering" - the illegal littering of public spaces - does not only cause costs for the environment and society, but also has significant financial consequences through increased cleaning costs. Much of the littering consists of "to-go" packaging, plastic bottles, and cigarette butts. Currently, the problem is predominantly addressed with laws, fines, and education campaigns. Politicians and the media are also putting the appearance of cities on the agenda, but classic instruments such as controls by municipal law enforcement officers and harsh sanctions against "litterers" are reaching their limits in solving the problem. In addition to classic environmental policy instruments, the tools of behavioral economics can make a complementary contribution in solving the problem: by influencing people's daily habits, green nudges can encourage people to reduce littering, thereby improving urban cleanliness. – – Die Nachfrage nach Sauberkeit in den deutschen Städten steigt: "Littering" - die illegale Vermüllung des öffentlichen Raums - verursacht nicht nur Kosten für die Umwelt und Gesellschaft, sondern hat auch erhebliche finanzielle Konsequenzen durch steigende Reinigungskosten. Ein Großteil des Litterings besteht aus 'To-Go'- Verpackungen, Plastikflaschen und Zigarettenstümmeln. Derzeit wird das Problem vor allem mit Gesetzen, Bußgeldern und Aufklärungskampagnen angegangen. Politiker und Medien setzen das Erscheinungsbild der Städte auf die Tagesordnung, klassische Instrumente wie Kontrollen durch kommunale Ordnungshüter und harte Sanktionen gegen 'Litterer' stoßen bei der Lösung des Problems jedoch an ihre Grenzen. Neben den klassischen umweltpolitischen Instrumenten können die Tools der Verhaltensökonomie einen ergänzenden Beitrag bei der Problemlösung leisten: Durch die gezielte Beeinflussung der täglichen Gewohnheiten können auf den Umweltschutz ausgerichtete 'Green Nudges' die Menschen dazu bewegen, Littering zu reduzieren, wodurch die Sauberkeit in den Städten verbessert werden kann.
Keywords: D91; H00; H23; 330